Semiotic Analysis of Beauty According to Roland's Barthes Theory in Relation to Indonesian and German Culture - Indira, Dian; Susilo, Catharina Dian Ikawati; Purnomowulan, N. R. (Nusantara Science and Technology Proceedings)
A beauty has long been an interesting and important topic for women around the world. The concept of beauty cannot be generalized to all women in all parts of the world. Beauty for one community group is different from beauty for the other community groups because beauty is closely related to culture. In the era of globalization, which is characterized by the ease of obtaining various information, the opportunity to learn about the beauty concepts of different countries is as wide open as possible. For this purpose, cosmetic advertisements in the mass media play an important role. However, there are signs in the advertisement that reflect cultural elements, which can be studied semiotically. This study uses a descriptive qualitative method. This paper is a semiotic study that aims to present the meaning of beauty myths for Indonesian and German women, which are first examined through denotative and connotative meanings. The theory used is the semiotic theory of Roland Barthes. To see the difference in beautiful concepts from two different cultures, the data of Nivea skin care ads with Indonesian and German version are taken. In the results, there are differences of Indonesian and German beauty concept closely related to culture. The message of the beautiful Indonesian version shows that the woman is attractive and has a white skin, while the German version shows that the attractive level and skin color are not a priority, but women with the healthy skin.